The vitellogenin receptor gene is involved in lifespan regulation of Zeugodacus cucurbitae (Coquillett) after short-term high-temperature treatment - Lian, Yuyang; Peng, Sihua; Yang, Xiaofeng; Jia, Jingjing; Li, Jinlei; Wang, Aqiang; Yang, Shuyan; Zheng, Rongjiao; Zhou, Shihao (Frontiers in Physiology, 2022)
Zeugodacus cucurbitae (Coquillett) is a highly damaging agricultural pest in many tropical and subtropical countries around the world and high temperatures usually affect its survival strategies. To clarify the effect of short-term high temperatures on the survival and lifespan of Z. cucurbitae, newly emerged adults of three consecutive generations (F1, F2, and F3) were exposed to 25 °C, 33 °C, 37 °C, 41 °C, and 45 °C treatments for 1 h. The effect of these tem-peratures on survival and lifespan was evaluated using indicators, such as lifespan and pupa-tion rate. Then, to study the molecular regulatory mechanism of lifespan in Z. cucurbitae after short-term high temperatures treatment, we exposed the newly emerged adults at 25 °C and 45 °C treatments for 1 h, and used siRNA to interfere with the expression of the female Vitel-logenin Receptor (VgR) gene to study the effect of the VgR gene on the lifespan of Z. cucurbi-tae. Results showed that the survival rate, lifespan, pupae weight, pupation rate, and emer-gence rate of Z. cucurbitae decreased with the increase of temperature, while the sex ratio in-creased. The heat resistance of females was higher than that of males. Interference with the expression of the VgR gene resulted in the significant shortening of the female's lifespan by about 60% after being exposed to 25 °C and 45 °C treatments for 1 h, which indicated that the VgR gene is involved in the lifespan regulation of Z. cucurbitae. This study can provide a reference for the integrated control of Z. cucurbitae in high-temperature seasons.